The Therapeutic Goals Set by University Students in an Anonymous Web-Based Therapy and Support Setting - Hanley, Terry; Prescott, Julie; Sefi, Aaron (Frontiers in Psychology, 2022)
The interest in student mental health and wellbeing has increased in recent years. Additionally, there is a rising volume of students seeking support. Numerous online resources have been developed to meet this need, including anonymous web-based therapy. To date there has been little focus upon how students may utilize such a service, and this study examines routine evaluation data (solicited from a Goal based Outcome Measure) from a UK based service provider. Over the course of one academic year (2018-2019), 211 students articulated therapeutic goals within Kooth Student, a web-based therapy and support service for individuals in higher education. These goals were examined for key trends. The students identified a total of 625 goals to work on in therapy, with individuals setting an average of three goals each. The most common goals focused upon obtaining additional support within the service and exploring their emotions. The results suggested that female students were more likely to move towards achieving their goals, with goals that did move shifting an average of 7.74 on a 10-point scale. Practical goals that focused upon getting more help, both inside and outside the service, were most likely to be achieved. In contrast, self-help/self-care goals were less likely to be achieved. These results provide a helpful insight into how students made use of therapy and highlight the importance of the interaction that web-based services have with other provision (web-based and in-person). They also demonstrate the challenge of capturing meaningful outcome data in anonymous services.